COMPARATIVE ASSESSMENT OF THE TECHNICAL EFFICIENCY OF MALE AND FEMALE BAMBARA NUT FARMERS IN NORTHEAST NIGERIA: A STOCHASTIC FRONTIER ANALYSIS APPROACH - Osayi, C.P.; Nnamerenwa, G.C.; Bulus, G. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study comparatively assessed the technical efficiency of male and female Bambara nut farmers in Northeast Nigeria using the Stochastic Frontier Analysis (SFA) approach. A multi-stage sampling procedure was used to select a total of 360 male and 360 female smallholder Bambara nut farmers from the study area. Data were collected using a structured questionnaire and analysed using Cobb-Douglas stochastic frontier cost function model and independent sample z-test. Findings revealed that male and female Bambara nut farmers have a mean Technical Efficiency level of 0.759 and 0.849 respectively. Female Bambara nut farmers are significantly more technically efficient (z = -12.560, p < 0.01) than their male counterparts. The major drivers of technical efficiency for both genders were farm size, labour, seed quantity, and agrochemical use, all of which were significant at p < 0.01. Factors influencing technical inefficiency also varied by gender. For male farmers, farming experience, labour use, seed quantity, and agrochemical application were significant at p < 0.01, while age, household size, cooperative membership, distance to farm, banditry/herdsmen attacks and training in Bambara nut farming were significant at p < 0.05. For female farmers, education, farming experience, cooperative membership, land ownership, and off-farm income were significant at p < 0.01, whereas age and herdsmen attacks were significant at p < 0.05. The study concluded that female Bambara nut farmers are more technically efficient than their male counterparts. Gender-sensitive agricultural extension services and training schemes need to be reinforced, in particular with attention to the inclusion of male farmers.